Use of Discrete, Continuous and Hybrid Petri Nets in Bio-modelling - Adam, Mansurah (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Petri net is a well-known field of mathematics and computer science, which has over the years been applied to problem solving in science and technology. Chemical processes, biomolecular systems, parallel and distributed computing, complex systems and the management of the flow of work are among areas where Petri nets has been successfully applied. This thesis examines application of discrete, continuous and hybrid Petri nets in bio-modelling. Throughout the study, we examine interrelationship between discrete and continuous components, making sure of compatibility of component types. Three case studies examined are; the bottling system, production system, and olive soap production.

ÖZ: Petri ağları, bilim ve teknoloji alanlarında problem çözmede yıllardan beri uygulanmış bir matematik ve bilgisayar bilimi alanıdır. Petri ağlarının başarıyla uygulandığı alanlar arasında kimyasal reaksiyonlar, biyomoleküler sistemler, paralel hesaplamalar, karmaşık yönetim sistemleri yer almaktadır. Bu tez, ayrık, sürekli ve hibrit Petri ağlarının biyo-modelleme uygulamalarını incelemektedir. Çalışma boyunca, ayrık ve sürekli bileşenler arasındaki ilişkiyi inceleyerek, bileşen türlerinin uyumluluğundan emin olduk. İncelenen üç çalışması; şişeleme sistemi, üretim sistemi ve zeytin sabunu üretimi.
Master of Science in Applied Mathematics and Computer Science. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2019. Supervisor: Prof. Dr. Rza Bashirov.
Keywords: Mathematics; Applied Mathematics and Computer Science; Petri nets--Computer science--Mathematics; Petri net; Bio-modelling; Discrete; Continuous; Hybrid; Simulation